THE EFFECT OF BALLOON BLOWING THERAPY IN PATIENTS WITH PPOK IN IMPROVING OXYGEN SATURATION - Sumarni, Ranti; Suwarni, Anik; Widiyono; Pradipto, Tegar (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
COPD is a disease of the respiratory system characterized by progressive and irreversible airway obstruction, accompanied by inflammation and systemic effects leading to airway narrowing and increased sputum production. This results in difficulty breathing and shortness of breath, which can be seen through increasingly strong contractions of the respiratory muscles. Prevention can be done through respiratory rehabilitation, such as blowing balloon exercise, which aims to better improve oxygen saturation. One way to measure this is by monitoring oxygen saturation. This study aims to determine the effect of balloon blowing on improving oxygen saturation in COPD patients. The research design used a one group pre-post design. The population of this study were patients with COPD, 30 samples were selected purposive sampling technique and data analysis using Wilcoxon test. The results showed that there was an effect of balloon blowing therapy on increasing oxygen saturation in COPD patients at UNS Hospital (p value 0.000). Researchers recommend that blowing balloon exercise be done regularly and consistently, with three blows every morning for three consecutive days, so that COPD patients can achieve more optimal oxygen saturation and reduce the risk of exacerbations. Keyword : COPD, Oxygen Saturation, Balloon Blowing Therapy